2017
DOI: 10.1093/gerona/glx148
|View full text |Cite
|
Sign up to set email alerts
|

FNIH-defined Sarcopenia Predicts Adverse Outcomes Among Community-Dwelling Older People in Taiwan: Results From I-Lan Longitudinal Aging Study

Abstract: Among community-dwelling older people in Taiwan, participants with FNIH-defined sarcopenia had a significantly greater risk of all-cause mortality and composite falls, emergency department visits, institutionalization, and hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 48 publications
1
37
0
Order By: Relevance
“…Secondly, we included relatively healthy participants because the baseline assessment was conducted in a community setting, which might be a constraint on the generalizability and applications to practice. Additionally, as the 24 month follow‐up period was relatively shorter than those in the previous studies, future studies should provide a longer follow‐up period for incident disability to clarify how the incidence of disability increases with advancing age.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Secondly, we included relatively healthy participants because the baseline assessment was conducted in a community setting, which might be a constraint on the generalizability and applications to practice. Additionally, as the 24 month follow‐up period was relatively shorter than those in the previous studies, future studies should provide a longer follow‐up period for incident disability to clarify how the incidence of disability increases with advancing age.…”
Section: Discussionmentioning
confidence: 94%
“…The associations between sarcopenia and clinical adverse outcomes (i.e. disability, fracture, and mortality) were also varied, depending on the definition of sarcopenia and the formula for calculating muscle mass …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarcopenia has been described as an age-related decline in skeletal muscle mass as well as muscle function 1 and leads to serious health problems, including disability. [2][3][4] It is important for the elderly to shorten the period of having a disability and prolong the period of being healthy. 5 Thus, the modifiable risk factors were particularly focused on that likely to contribute to develop intervention from sarcopenia.…”
Section: Introductionmentioning
confidence: 99%
“… 36 , 37 Recently, FNIH-defined sarcopenia criteria have been reported to predict death and adverse events from I-Lan Longitudinal Aging Study in Taiwan. 38 However, we showed that only a sarcopenia definition with height-adjusted muscle index was significantly associated with death or institutionalization, rather than FNIH sarcopenia criteria when adjusted for age and sex. This difference may be due to heterogeneities in the characteristics of the study population, outcome measures, and the duration of follow-up.…”
Section: Discussionmentioning
confidence: 64%